Pharmacogenomics β-Blockers in Cardiovascular Disease: Implications for Blood Pressure and Clinical Outcomes - Zulqifli, Iqbal; Malau, Jekmal; Aditya, Fitra Ari; Nursyafillah, Rizki Noval; Harbulcholizi, Luthfi; Rahmasari, Ratika; Raekiansyah, Muhareva; Hermosaningtyas, Anastasia Aliesa (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Hypertension is a chronic condition that increases the risk of cardiovascular disease and death. β-blockers, including atenolol, metoprolol, bisoprolol, and carvedilol, lower blood pressure by blocking adrenergic receptors. However, variations in response and side effects are often influenced by genetic differences that affect drug metabolism and action. This narrative review analyzes studies published between 2014 and 2024 in PubMed, ScienceDirect, and Google Scholar using keywords related to genetic variation, β-blockers, hypertension, pharmacogenetics, and polymorphisms. Original studies in English, clinical trials on genetic polymorphisms and β-blocker response were included; reviews and incomplete studies were excluded. Clinical outcomes included changes in systolic and diastolic blood pressure, heart rate, hypotension, aortic root z-score, LVOT gradient, NT-proBNP, and premature ventricular contractions, which were associated with polymorphisms in the ADRB1, ADRB2, ACY3, FGD5, SLC4A1, and SLC25A31 genes. Metabolic outcomes, impaired fasting glucose, new-onset diabetes, and melatonin metabolite changes were associated with variants in PRKCB, DPYS, PAH, and PLEKHH2. Most data came from European and North American populations, with limited representation from Asia, limiting generalizability. These findings support the use of pharmacogenomics to personalize β-blocker therapy and improve hypertension management, despite challenges related to high costs, limited infrastructure, the lack of clinical guidelines, and population heterogeneity.